Local strain energy density for the fatigue assessment of hot dip galvanized welded joints: some recent outcomes - M. Peron; SMJ. Razavi; F. Berto; J. Torgersen; F. Mutignani (Fracture and Structural Integrity)
Since in literature only data about the effect of the hot-dip galvanizing coating on fatigue behavior of unnotched specimens are available, whereas very few for notched components and none for welded joints, the aim of this paper is to partially fill this lack of knowledge comparing fatigue strength of uncoated and hot-dip galvanized fillet welded cruciform joints made of structural steel S355 welded joints, subjected to a load cycle R = 0. 34. The results are shown in terms of stress range ?s and of the averaged strain energy density range DW in a control volume of radius R0 = 0.28 mm